Interactive Storybook Design for Developing Early Childhood Numeracy Literacy: Desain Buku Cerita Interaktif untuk Mengembangkan Literasi Numerasi Anak Usia Dini - Astiawati, Eka (Universitas Muhammadiyah Sidoarjo, 2025)
Background: Early numeracy literacy is a fundamental component of cognitive development, yet studies and PISA 2022 results reveal that Indonesian children still perform below international standards. Specific background: This limitation is partly due to the scarcity of engaging and interactive learning media that contextualize mathematical concepts. Knowledge gap: Previous digital learning tools often separated storytelling from numerical learning, reducing children’s engagement. Aims: This study aimed to develop and validate an interactive storybook—Petualangan Seru Qiqi—based on the SMART principles (Simple, Measurable, Attractive, Relevant, and Applicable) to foster early numeracy skills. Results: Using a Research and Development (R&D) 4D model (Define, Design, Develop, Disseminate), expert validation confirmed the book’s high feasibility (average 89.3%), while the paired t-test showed a significant improvement in children’s numeracy scores (mean difference = 9.47, p = 0.001). Novelty: The product uniquely integrates storytelling with embedded numerical challenges in a multisensory digital format. Implications: The findings demonstrate that interactive storybooks can serve as a practical, pedagogically sound innovation for teachers and curriculum developers in early childhood education. Highlight The SMART-based interactive storybook effectively supports early numeracy learning. Validation and testing confirm its pedagogical and technological feasibility. The model provides a replicable framework for future digital learning innovations. KeywordInteractive Storybook, Early Childhood Education, Numeracy Literacy, SMART Framework, Digital Learning Media